Konstruksi Pendidikan Islam Berbasis Rahmatan Lil’alamin; Suatu Telaah Diskursif - Fauzi, Ahmad (LP3M Universitas Islam Zainul Hasan Genggong, 2018)
Islamic education today, faced with increasingly crucial challenges, the view, not separated from the atmosphere of modernization and globalization. Therefore, the presence of Islamic education is required to play its role dynamically and is expected to provide social change in the midst of pluralistic society life. Thus to build Islamic education in Indonesia that can bring the vision of universal Islam, it is necessary paradigm of Islamic education based rahmatan lilalamin, by promoting several principles, among others; maintaining harmony, peace, mutual respect, liberation, not the contrary as domestication and social domestication. In that context, the educational portrait referred to, is seen as a socio-cultural enlightment. Therefore, the effort to build the paradigm of Islamic education in question is a necessity, this can be done by restoring the social values of Islamic education universally (kaffah), in addition to being dynamic (inclusive), through several stages, namely (a) build awareness inclusive by transmitting the whole system of religious social values such as ketauhidan, tolerance and fairness into the structure of the curriculum as culture domination and control. (b) reconstructing the Islamic educational paradigm from the perspective of indoctrination to participatory, (c) changing the ideological paradigm to being scientific by allowing the human mind to study and develop knowledge through his guidance. Keywords: Construction, Islamic Education based on Rahmatan Lil, alamin